2012
DOI: 10.1007/s10103-012-1180-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimal and safe treatment of spider leg veins measuring less than 1.5 mm on skin type IV patients, using repeated low-fluence Nd:YAG laser pulses after polidocanol injection

Abstract: Treatment of micro-veins of less than 1.5 mm with laser and with chemical sclerosis is technically challenging because of their difficulty to remedy. Laser treatment is even more difficult when dark phototypes are involved.Three groups of 30 patients each, skin type IV, and vessels measuring less than 1.5 mm in diameter, were enrolled for two treatment sessions 8 weeks apart: group A, polidocanol (POL) micro-foam injection; group B, Nd:YAG laser alone; and group C, laser after POL injection. Repeated 8-Hz low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…226 In the same way, comparison data are missing regarding the potential combination of sclerotherapy followed by Nd:YAG treatment: an option that has been proposed already more than 15 years ago. 227 To the contrary, data show no benefit in combining pulsed dye laser with sclerotherapy. 228 Innovative devices combining diode laser and radiofrequency emission have been reported in the literature, yet without a direct comparison with laser only treatment.…”
Section: Discussionmentioning
confidence: 99%
“…226 In the same way, comparison data are missing regarding the potential combination of sclerotherapy followed by Nd:YAG treatment: an option that has been proposed already more than 15 years ago. 227 To the contrary, data show no benefit in combining pulsed dye laser with sclerotherapy. 228 Innovative devices combining diode laser and radiofrequency emission have been reported in the literature, yet without a direct comparison with laser only treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For small leg veins (0.5-2 mm), the Nd:YAG laser may be equivalent to sclerotherapy. A recent study using an Nd:YAG laser immediately after polidocanol sclerotherapy resulted in a statistically significant improvement over sclerotherapy or laser alone [26]. Another similar study yielded similar findings [27].…”
Section: Leg Veinsmentioning
confidence: 71%
“…It was confirmed that the properties of both POL and the Nd:YAG laser could be altered when certain conditions were achieved. [7][8][9] The presence of POL foam bubbles inside the vessel while applying pulse lengths and fluences lower than those used by other authors is required. [7][8][9][10] Another study assessed the efficacy of this method in the treatment of spider leg veins measuring less than 1.5 mm, on skin type IV patients, comparing the results of the combined therapy (POL þ Laser) with those obtained when only POL or the Nd:YAG laser, separately, were applied.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The presence of POL foam bubbles inside the vessel while applying pulse lengths and fluences lower than those used by other authors is required. [7][8][9][10] Another study assessed the efficacy of this method in the treatment of spider leg veins measuring less than 1.5 mm, on skin type IV patients, comparing the results of the combined therapy (POL þ Laser) with those obtained when only POL or the Nd:YAG laser, separately, were applied. The combined treatment produced a considerable improvement in the clearing of veins in the short term (three months after treatment), in comparison to both treatments in isolation, but the results could not be proven to be permanent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation